“Não nos embaracemos com os dias santos, trabalhemos”: deputados da Província do Maranhão na Câmara dos Deputados (1826-1829) - BEZERRA, Mário Augusto Carvalho (2020)
This dissertation proposes to analyze the political performance of the deputies of Maranhão, in the first legislature of the General Legislative Assembly of the Empire of Brazil (1826- 1829), starting from the political-administrative process of recognition of the political authority of Rio de Janeiro; and, of the elections for general deputies in the province of Maranhão, in 1825. The analysis points to the unfolding and dynamization of the Maranhão bench in terms of the defense of the provincial interests and of the nation, organization and maintenance of the national political unity, concentrating the discussion in the first legislature of the Chamber of Deputies (1826-1829). Elected in June 1825, Francisco Gonçalves Martins, João Bráulio Muniz, Manoel Telles da Silva Lobo and Manuel Odorico Mendes, went through a lengthy electoral process motivated by the political reorganization of the province. After passing through the University of Coimbra, they worked in the political scenario of Maranhão during the process of Maranhão's “adhesion” to the Empire; in the period that corresponds to the institutional consolidation of the Empire and the formation of Brazilian national unity, focusing on the political debates of Maranhão's deputies and the defense of provincial interests, before or in accordance with the national state, under construction. Important theme for the studies of the Nineteenth century, as it contributes to the unveiling of key issues of center-province relations from Maranhão, whose political representation in Rio de Janeiro, in the early years of the Empire, lacks approaches in Maranhão's historiography.